2019 International Conference on ReConFigurable Computing and FPGAs (ReConFig) 2019
DOI: 10.1109/reconfig48160.2019.8994789
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Ring Oscillator based Sensors for Remote Side-Channel Attacks on FPGAs

Abstract: FPGAs have been widely adopted in cloud datacenters and System-on-Chip for hardware acceleration purposes during the past few years. For flexibility and efficiency reasons, cloud FPGA fabrics are likely to be shared between multiple users. Despite the logical isolation suggested to protect each tenant, multiuser FPGA environment raises crucial questions about the potential security threats that it may represent. Recently, a series of papers demonstrated that a malicious user could be able to use its rented log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Schellenberg et al [13] proposed first RPA attack using TDC sensors to deduce the secret key of an AES circuit. Gravellier et al [15] proposed to use RO based sensors to detect voltage fluctuations.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Schellenberg et al [13] proposed first RPA attack using TDC sensors to deduce the secret key of an AES circuit. Gravellier et al [15] proposed to use RO based sensors to detect voltage fluctuations.…”
Section: Related Workmentioning
confidence: 99%
“…These power dissipations are quantized by an oscilloscope or a sensor such as, TDC or RO-based voltage sensor. Authors in [13] and [15] have shown how AES is vulnerable to RPA attack using TDC and RO sensors. Then the adversary builds hypothetical power dissipation, such as hamming weight (counting number of '1's) or hamming distance (counting the number of bit flips), to model what circuit might consume based on input/ output using a guessed key.…”
Section: B Correlation Power Analysis-cpa Attacksmentioning
confidence: 99%
See 3 more Smart Citations